KEBIJAKAN FORMULASI HUKUM PIDANA TERHADAP “JUSTICE COLLABORATOR” DALAM TINDAK PIDANA KORUPSI DI INDONESIA - Oly Viana Agustine, Eko Soponyono, Pujiyono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Policies in making a good criminal law essentially inseparable from crime prevention efforts. Corruption is the behavior of public officials who illegally enrich themselves or others, the abuse of public power. Need to break the law to accelerate the eradication of corruption is to play the role of justice collaborator. But positive law, not to encourage people to take part as a justice collaborator